2015
DOI: 10.2319/050914-334.1
|View full text |Cite
|
Sign up to set email alerts
|

Camouflage effects following resin infiltration of postorthodontic white-spot lesions in vivo: One-year follow-up

Abstract: Objective: To assess camouflage effects by concealment of postorthodontic white-spot lesions (WSLs) to sound adjacent enamel (SAE) achieved over 12 months with resin infiltration (Icon, DMG, Hamburg, Germany). Methods: Twenty subjects (trial teeth n teeth 5 111) who had received resin infiltration treatment of noncavitated postorthodontic WSLs were contacted for a 1-year follow-up assessment of CIE-L*a*b* colors (T12). Color and lightness (CIE-L*a*b*) data for WSLs and SAE were compared to baseline data assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
78
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(86 citation statements)
references
References 24 publications
(36 reference statements)
2
78
0
6
Order By: Relevance
“…The effect of lesion progression as seen in approximal lesions was confirmed for labial lesions, also (34,36) . Furthermore, case reports and short-term studies (9,32,34,35,(37)(38)(39)(40)(41)(42)(43)(44)(45) describe a masking of WSL, up until 1 year following infiltration (32,37,46) . Hammad et al distinguished between infiltration of visible WSLs without surface disruption and WSLs with a roughened surface not requiring restoration, and reported significant improvement in both groups following infiltration.…”
Section: Post-orthodontic Wsl In Vivomentioning
confidence: 99%
“…The effect of lesion progression as seen in approximal lesions was confirmed for labial lesions, also (34,36) . Furthermore, case reports and short-term studies (9,32,34,35,(37)(38)(39)(40)(41)(42)(43)(44)(45) describe a masking of WSL, up until 1 year following infiltration (32,37,46) . Hammad et al distinguished between infiltration of visible WSLs without surface disruption and WSLs with a roughened surface not requiring restoration, and reported significant improvement in both groups following infiltration.…”
Section: Post-orthodontic Wsl In Vivomentioning
confidence: 99%
“…Infiltration of fresh and more superficial lesions have been reported to be much easier compared to older, deeper-seated lesions with thicker pseudo-intact surface layers (Knösel et. al., 2013;Eckstein et al). The latter require several repetitions of etching intervals; the same seems to hold true for infiltration of brown spots (Knösel et.…”
Section: Discussionmentioning
confidence: 99%
“…Knösel et al performed a split-mouth controlled RCT on the subject of the durability of the achieved esthetic effects of WSL infiltration. They found that there was an assimilation of WSL color to surrounding enamel following infiltration that was color stable, without significant changes over at least 12 months (Knösel et al, 2013;Eckstein et al). Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations